Preliminary screening of biomarkers and drug candidates in a mouse model of β-thalassemia based on quasi-targeted metabolomics - Guo, Xianfeng; Zhang, Xuchao; Li, Min; Peng, Yuanliang; Wang, Zi; Liu, Jing (Frontiers in Physiology, 2024)
β-thalassemia (β-TH) is a hereditary hemolytic anemia that results in deficient hemoglobin (Hb) synthesis and characterized by ineffective erythropoiesis, anemia, splenomegaly, and systemic iron overload. Herein we applied quasi-targeted metabolomics between wild type (Wt) and heterozygous β-TH mice (Th3/+), a model of non-transfusion-dependent β-TH intermedia, in plasma and peripheral blood (PB) cells. Using Kyoto encyclopedia of genes genomes (KEGG) enrichment analysis, we found that taurine and hypotaurine metabolism disorders in plasma and alanine, aspartate and glutamate metabolism disorders in PB cells. After systematically anatomize the metabolites by machine algorithms, we confirmed that alpha-muricholic acid UP , N-acetyl-DL-phenylalanine UP in plasma and Dl-3-Hydroxynorvaline UP , O-Aceyl-L-Serine UP , H-Abu-OH UP , S-(Methyl)Glutathione UP , Sepiapterin DOWN , Imidazoleacetic acid DOWN in PB cells play key roles in predicting the occurrence of β-TH. Furthermore, Sepiapterin, Imidazoleacetic acid, Methyl alpha-D-glucopyranoside and alpha-ketoglutaric acid ha a good binding capacity to hemoglobin E through molecular docking which considered to be potential drug candidates for β-TH. Those results may help in identifying useful molecular targets in the diagnosis and treatment of β-TH and lays a strong fundation for further research.